2002
DOI: 10.1063/1.1479141
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of anions and cations in cesium hydrogensulfide (CsHS, CsDS): Neutron and x-ray diffraction, calorimetry and proton NMR investigations

Abstract: Protonated and deuterated samples of the hydrogensulfide of cesium were studied by high-resolution neutron powder diffraction, calorimetry and proton NMR investigations in a wide temperature range. Primarily due to reorientational disorder of the anions, three modifications of the title compounds are known: an ordered low-temperature modification- LTM (tetragonal, I4/m, Z=8), a dynamically disordered middle- temperature modification-MTM (tetragonal, P4/mbm, Z=2), and a high-temperature modification-HTM (cubic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…1,2 At 141°C, CsHSO 4 undergoes a phase transition from a low conductivity phase to a high conductivity phase ͑superprotonic phase͒ with the disorder of a hydrogen bond network. [3][4][5][6][7][8][9] It has been reported that a steep increase in conductivity by four orders of magnitude takes place, giving a value of 10 Ϫ2 S cm Ϫ1 , due to a structural transformation. 3 For practical applications, CsHSO 4 is also noteworthy, as confirmed by the recent successful demonstration of a fuel cell fabricated with CsHSO 4 electrolyte.…”
mentioning
confidence: 99%
“…1,2 At 141°C, CsHSO 4 undergoes a phase transition from a low conductivity phase to a high conductivity phase ͑superprotonic phase͒ with the disorder of a hydrogen bond network. [3][4][5][6][7][8][9] It has been reported that a steep increase in conductivity by four orders of magnitude takes place, giving a value of 10 Ϫ2 S cm Ϫ1 , due to a structural transformation. 3 For practical applications, CsHSO 4 is also noteworthy, as confirmed by the recent successful demonstration of a fuel cell fabricated with CsHSO 4 electrolyte.…”
mentioning
confidence: 99%